2016
DOI: 10.1111/jvec.12190
|View full text |Cite
|
Sign up to set email alerts
|

What is the ‘true’ effect ofTrypanosoma rangelion its triatomine bug vector?

Abstract: The phrase, "T. rangeli is pathogenic to its insect vector, " is commonly found in peer-reviewed publications on the matter, such that it has become the orthodox view of this interaction. In a literature survey, we identified over 20 papers with almost the exact phrase and several others alluding to it. The idea is of particular importance in triatomine population dynamics and the study of vector-borne T. cruzi transmission, as it could mean that triatomines infected with T. rangeli have lower fitness than uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…On the other hand, Gottdenker et al [ 28 ] postulated that T. rangeli / T. cruzi co-infection may confer a survival advantage for R. pallescens throughout adulthood. The same conclusion was reached by Peterson & Graham [ 27 ] who observed that R. prolixus experimentally co-infected with T. cruzi and T. rangeli have higher survival than bugs infected with just one of the species. In any case, a better evaluation of the occurrences and consequences of the infection with T. cruzi and/or T. rangeli in the dark variant of R. pallescens is necessary.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…On the other hand, Gottdenker et al [ 28 ] postulated that T. rangeli / T. cruzi co-infection may confer a survival advantage for R. pallescens throughout adulthood. The same conclusion was reached by Peterson & Graham [ 27 ] who observed that R. prolixus experimentally co-infected with T. cruzi and T. rangeli have higher survival than bugs infected with just one of the species. In any case, a better evaluation of the occurrences and consequences of the infection with T. cruzi and/or T. rangeli in the dark variant of R. pallescens is necessary.…”
Section: Resultssupporting
confidence: 77%
“…These high infection frequencies with T. rangeli seem to be inconsistent with the described pathological effects of T. rangeli for its vectors [ 26 ]. Recently, Peterson & Graham [ 27 ] also called attention to the lack of sufficient evidence to support the assumption that T. rangeli is pathogenic to all Rhodnius species. On the other hand, Gottdenker et al [ 28 ] postulated that T. rangeli / T. cruzi co-infection may confer a survival advantage for R. pallescens throughout adulthood.…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies in Panama have shown that T. cruzi infection in R. pallescens increases in response to anthropogenic disturbance (Gottdenker et al 2012). Furthermore, R. pallescens is frequently co-infected by T. cruzi congeneric T. rangeli , a trypanosome species that is entomopathogenic in experimentally infected Rhodnius prolixus , but is not believed to cause disease in mammals (Groot and Hernandez Mora, 1947; Groot et al 1951; Herbig-Sandreuter, 1957; Añez, 1981; Añez et al 1985; Nieves and Añez, 1992; Peterson and Graham, 2016). Trypanosoma rangeli is epidemiologically important, as it shares 60% of its antigens with T. cruzi , and the two parasites can cross-react in serological tests (Guhl and Marinkelle, 1982; Saldana & Sousa, 1996 a , b ; Guhl and Vallejo, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Co-infection with T. cruzi and T. rangeli occurred in 73.5% of analyzed triatomines. Despite earlier reports suggesting T. rangeli infection is pathogenic to triatomines, more recent studies point to the need of more solid evidence before generalizing this claim [72]. Indeed, recent reports suggest co-infection increases R. prolixus survival, reproduction and fitness, which in turn would favor transmission of both parasite species [73].…”
Section: Trypanosoma Rangeli and T Cruzi Genetic Diversitymentioning
confidence: 97%